2021
DOI: 10.1111/anu.13324
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microalgae concentrate as diet for hard clam, Mercenaria mercenaria , larvae

Abstract: The on-site culture of live microalgae represents a major challenge for bivalve hatchery operations due to high cost and labour demands. This study evaluated the efficacy of commercially available microalgae concentrates as a partial or complete replacement diet for live microalgae for culture of the hard clam, Mercenaria mercenaria, larvae.Larvae were fed from D-larval stage to post-set, 2-14 days post fertilization (DPF).Larvae fed the complete replacement diets were significantly smaller than those fed part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Higher settlement and biofouling were also observed in this study at a greater frequency in tanks in which concentrates were fed compared with tanks receiving live microalgae only. This was noted previously with larval hard clams (Hassan et al 2021), even though concentrates were passed through a 20-μm screen prior to tank addition to circumvent clumping. Southgate et al (2016) also reported problems with the clumping of concentrates fed to winged pearl oysters.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Higher settlement and biofouling were also observed in this study at a greater frequency in tanks in which concentrates were fed compared with tanks receiving live microalgae only. This was noted previously with larval hard clams (Hassan et al 2021), even though concentrates were passed through a 20-μm screen prior to tank addition to circumvent clumping. Southgate et al (2016) also reported problems with the clumping of concentrates fed to winged pearl oysters.…”
Section: Discussionmentioning
confidence: 93%
“…For this study, two of these products (ISO 1800 and Shellfish Diet 1800) were chosen, as a previous study showed that the survival and growth of hard clam larvae were significantly decreased with both (Hassan et al 2021). Both products are advocated for use with bivalve larvae, juveniles, and broodstock; however, the Shellfish Diet contains a mixture of microalgal species, including some of which are diatoms that may be too large for larvae to ingest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial replacement of live microalgae using diferent types of formulated diets has been reported for facilitating the aquaculture of a number of species of bivalves. For example, yeast-based diets [21], lipid emulsion [22], microcapsule [23], bacteria [24], and microalgal pastes [25,26] have been used to partially substitute live microalgae for rearing juvenile shellfsh. For example, a replacement of 20% of the dried microalgae Tetraselmis suecica, 80% of yeast and up to 81% of mixed microcapsules and yeast has been found to be a satisfactory diet for juvenile oysters (Crassostrea gigas and Ostrea edulis) and the clams (Mercenaria mercenaria and Ruditapes philippinarum) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Past research has evaluated the correlation between the gross biochemical composition of the diet and juvenile hard clam growth (Epifanio, 1979; Wikfors et al., 1992). To improve understanding of the dietary requirements for hard clam hatchery production, our lab has recently evaluated live microalgae and microalgae concentrate diets for larvae (Hassan et al., 2021a, 2021b) and the variations of filtration and ingestion rates of various microalgae species by larvae and juveniles (Hassan et al., 2022). This study aims to identify an optimal microalgae diet based on growth, survival and fatty acid profile for the culture of hard clam juveniles using combinations of T. lutea , P. lutheri , Chaetoceros gracilis and Cyclotella nana .…”
Section: Introductionmentioning
confidence: 99%